(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article presents the results of a complex analysis of the processes of forming assortments and creating a production program in sewing and knitting enterprises. The procedure for determining the volume of production and determining the consumption of knitted fabric per item is given.